Magnetic Nanoparticle Based Nonviral MicroRNA Delivery into Freshly Isolated CD105+ hMSCs - Anna Schade; Paula Müller; Evgenya Delyagina; Natalia Voronina; Anna Skorska; Cornelia Lux; Gustav Steinhoff; Robert David (Stem Cells International)
Genetic modifications of bone marrow derived human mesenchymal stem cells (hMSCs) using microRNAs (miRs) may be used to improve their therapeutic potential and enable innovative strategies in tissue regeneration. However, most of the studies use cultured hMSCs, although these can lose their stem cell characteristics during expansion. Therefore, we aimed to develop a nonviral miR carrier based on polyethylenimine (PEI) bound to magnetic nanoparticles (MNPs) for efficient miR delivery in freshly isolated hMSCs. MNP based transfection is preferable for genetic modifications in vivo due to improved selectivity, safety of delivery, and reduced side effects. Thus, in this study different miR/PEI and miR/PEI/MNP complex formulations were tested in vitro for uptake efficiency and cytotoxicity with respect to the influence of an external magnetic field. Afterwards, optimized magnetic complexes were selected and compared to commercially available magnetic vectors (Magnetofectamine, CombiMag). We found that all tested transfection reagents had high miR uptake rates (yielded over 60%) and no significant cytotoxic effects. Our work may become crucial for virus-free introduction of therapeutic miRs as well as other nucleic acids in vivo. Moreover, in the field of targeted stem cell therapy nucleic acid delivery prior to transplantation may allowfor initial cell modulation in vitro.